РАЗВИТИЕ ТВОРЧЕСКИХ КАЧЕСТВ УЧИТЕЛЯ НАЧАЛЬНЫХ КЛАССОВ (Scientific journal of the Fergana State University, 2024)
In this article, there are recommendations that should be implemented in order to develop the creative qualities of primary school teachers, increase their potential, and enrich their worldview. The research analyzes the importance of advanced pedagogic activity in modern society and examines its problems in the context of various disciplines. Based on the introduction of educational technologies, the importance of scientific approaches and practical strategies in solving problems related to the methods and methods of developing creative thinking is emphasized. . Approaches aimed at improving students' reading abilities by understanding the problem of the modern teacher, its social, psychological and pedagogical consequences are discussed. The study also sheds light on various factors that influence the learning process. task is to teach children self-awareness, self-control, self-discipline, to teach them to make the right choice, to teach them to think creatively. The results suggest different didactic and therapeutic methods that can be used to solve the problems related to the pedagogue. Therefore, this article talks about the need for primary school teachers to constantly work on themselves.